2021
DOI: 10.21203/rs.3.rs-131380/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-dependent pathogenic characteristics of SARS-CoV-2 infection in ferrets

Abstract: The sero-prevalence of SARS-CoV-2 in healthy people is not significantly different among age groups, but persons age 65 years or older had strikingly higher COVID-19 mortality compared to younger individuals. To understand COVID-19 manifestations in patients of different ages, ferrets in three age groups were infected with SARS-CoV-2. Although SARS-CoV-2 was isolated from all ferrets regardless of age, aged ferrets (≥3 years old) showed higher viral load, longer nasal virus shedding, and more severe lung infla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Our findings showing higher susceptibility of aged ferrets to SARS-CoV-2 infection in the present study mirror clinical observations in humans, which point to increased susceptibility and higher levels of virus replication in the respiratory tract of older people when compared to young children 12,14 . Additionally, results presented here corroborate findings of a recent study by Kim and collaborators 35 , who showed age-related differences in viral load in the respiratory tract, and lung histopathology in ferrets inoculated with SARS-CoV-2. This study also showed that expression levels of genes related to the interferon (IFN) pathway, activated T cells, and macrophage responses were increased in older ferrets following SARS-CoV-2 infection 35 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings showing higher susceptibility of aged ferrets to SARS-CoV-2 infection in the present study mirror clinical observations in humans, which point to increased susceptibility and higher levels of virus replication in the respiratory tract of older people when compared to young children 12,14 . Additionally, results presented here corroborate findings of a recent study by Kim and collaborators 35 , who showed age-related differences in viral load in the respiratory tract, and lung histopathology in ferrets inoculated with SARS-CoV-2. This study also showed that expression levels of genes related to the interferon (IFN) pathway, activated T cells, and macrophage responses were increased in older ferrets following SARS-CoV-2 infection 35 .…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, results presented here corroborate findings of a recent study by Kim and collaborators 35 , who showed age-related differences in viral load in the respiratory tract, and lung histopathology in ferrets inoculated with SARS-CoV-2. This study also showed that expression levels of genes related to the interferon (IFN) pathway, activated T cells, and macrophage responses were increased in older ferrets following SARS-CoV-2 infection 35 . These changes are likely due to enhanced immune responses following higher viral replication in aged animals.…”
Section: Discussionsupporting
confidence: 91%
“…Since ferrets develop no or relatively mild disease and histopathological changes, combined with RT-PCR detectable viral loads and shedding from the respiratory tract, ferrets are regarded an optimal model for asymptomatic or mild disease in humans and are often used in transmission studies [ 92 ]. Recently, it was shown that aged ferret (>3 years old) have higher viral loads, longer shedding and more severe lung inflammatory cell infiltration, accompanied by more clinical symptoms (fever and weight loss) compared to juvenile and young adult ferrets [ 93 ].…”
Section: Experimental Sars-cov-2 Transmission Studies: Ferretsmentioning
confidence: 99%
“…158,159 Intranasal inoculation of SARS-CoV-2 induces the clinical symptoms that observed in COVID-19 patients, including reduced activity, nasal discharge, sneezing, wheezing, occasional cough, and increased body temperature in infected ferrets. 160,161 The clinical symptoms are manifested on 2 dpi and recover to the initial state on 12 dpi. The body weight loss is controversial in several studies on SARS-CoV-2-infected ferrets.…”
Section: Ferret Modelsmentioning
confidence: 99%